Culture-Free Enumeration of Mycobacterium tuberculosis in Mouse Tissues Using the Molecular Bacterial Load Assay for Preclinical Drug Development - Dimitrios Evangelopoulos; Carolyn M. Shoen; Isobella Honeyborne; Simon Clark; Ann Williams; Galina V. Mukamolova; Michael H. Cynamon; Timothy D. McHugh (Microorganisms, 2022)
Background: The turnaround times for phenotypic tests used to monitor the bacterial load of Mycobacterium tuberculosis, in both clinical and preclinical studies, are delayed by the organism’s slow growth in culture media. The existence of differentially culturable populations of M.tuberculosis may result in an underestimate of the true number. Moreover, culture methods are susceptible to contamination resulting in loss of critical data points. Objectives: We report the adaptation of our robust, culture-free assay utilising 16S ribosomal RNA, developed for sputum, to enumerate the number of bacteria present in animal tissues as a tool to improve the read-outs in preclinical drug efficacy studies. Methods: Initial assay adaptation was performed using naïve mouse lungs spiked with known quantities of M. tuberculosis and an internal RNA control. Tissues were homogenised, total RNA extracted, and enumeration performed using RT-qPCR. We then evaluated the utility of the assay, in comparison to bacterial counts estimated using growth assays on solid and liquid media, to accurately inform bacterial load in tissues from M. tuberculosis-infected mice before and during treatment with a panel of drug combinations. Results: When tested on lung tissues derived from infected mice, the MBL assay produced comparable results to the bacterial counts in solid culture (colony forming units: CFU). Notably, under specific drug treatments, the MBL assay was able to detect a significantly higher number of M. tuberculosis compared to CFU, likely indicating the presence of bacteria that were unable to produce colonies in solid-based culture. Additionally, growth recovery in liquid media using the most probable number (MPN) assay was able to account for the discrepancy between the MBL assay and CFU number, suggesting that the MBL assay detects differentially culturable sub-populations of M. tuberculosis. Conclusions: The MBL assay can enumerate the bacterial load in animal tissues in real time without the need to wait for extended periods for cultures to grow. The readout correlates well with CFUs. Importantly, we have shown that the MBL is able to measure specific populations of bacteria not cultured on solid agar. The adaptation of this assay for preclinical studies has the potential to decrease the readout time of data acquisition from animal experiments and could represent a valuable tool for tuberculosis drug discovery and development.